Design, Simulation, and Implementation of Connected IoT Wearable Devices in Healthcare Applications: IoT Wearable Devices in Healthcare Applications - Bagneid, Karim; Sherif, Youssef; Soliman, Maryam; Hussein, Mohamed (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2022)
Internet of Things (IoT) is one of the most versatile tools in modern technology and can be applied in many different domains. But one domain has started proving its need for more IoT-based systems and healthcare businesses. The main objective of this paper is to design, simulate, and implement a connected IoT-Health Care system to assist patients needing constant care and monitoring. This system is based on an integrated wearable device containing several sensors that detect and record the patient’s health information. This data will then be saved on an online database that is easily monitored and controlled through a mobile application to keep the personnel responsible for the patient’s care, constantly up to date with any recordings or alarms from the patient.